Incipient loss of flagella in the genus Geolegnia: the emergence of a new clade within Leptolegnia? - Steciow, Mónica Mirta (2013)
The genus Geolegnia represents a poorly documented group of saprolegnialean oomycetes isolated from soils as free-living organisms. Although it is morphologically similar to the facultative parasitic genus Leptolegnia, Geolegnia presents the uncommon property of having lost a flagellate stage in its lifecycle. Based on ITS and large subunit (LSU) rRNA sequence data, we show Geolegnia to be basal to Leptolegnia, and also introduce Geolegnia helicoides sp. nov. Using sequence data of Leptolegnia available in GenBank, supplemented by data derived from culture collections, we show that Geolegnia is nested within Leptolegnia, a genus characterised by its “conventional” biflagellate life cycle. The emergence of Geolegnia is therefore seen as a recent event, and we suggest here an evolutionary context where this loss might have been advantageous. Based on this study, Leptolegnia remains paraphyletic, awaiting the redefinition of genera in this complex.